(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This paper reports on an exploratory study examining parental involvement in preschool-level English language learners’ use of smartphone apps in a Chinese context. The study aimed at understanding the challenges that parents experienced, and how they responded to these in their engagement with their children’s mobile-assisted language learning. We collected data from 12 parents using surveys, daily records, and semi-structured interviews. The data analysis revealed that the parents participated in their children’s smartphone-based English learning by regulating their involvement time and selecting the learning content in response to their children’s needs. The findings suggest that parents’ knowledge of using smartphone apps and their awareness of the English language, as essential cultural capital, increased their active involvement in their children’s English learning. They also faced challenges such as English knowledge constraints and the perceived risks associated with children’s smartphone exposure. The results highlight the need for schools and teachers to support parents’ efforts to get effectively involved in their children’s smartphone-based language learning through modelling, reinforcement, and direct instruction.